Labor market news and expectations about jobs & earnings - Bernhard Schmidpeter (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
I show that workers update expectations about job search and salary growth when exposed to labor market news. To identify the impact of news on expectations, I exploit Foxconn's announcement to build a large production plant in Racine County, Wisconsin. Exposure to positive news leads to an increase in expected salary growth at the current firm, with no discernible differences between workers who are optimistic about receiving any outside offer in the future and those who are not. This suggests that firms and workers bargain frequently over wages, even in the absence of an outside job offer. Moreover, I find that individuals revise their expectations about potential outside wage offers upward, anchoring their beliefs in Foxconn's publicly announced wages. Investigating whether individuals act on their updated beliefs, I find evidence that exposure to the news leads to a small increase in current consumption. Using Foxconn's later announcement of a scaled down version of the initial investment plan, I find that individuals revise their expectations back toward baseline.
Keywords: C33; D84; E24; J31; J63; 330; Beliefs formation; wage expectations; outside options; consumption